Design and Analysis of the Dual Axis Tracking System for Solar Thermal Concentrator in Erbil City using Arduino Controller - Ramyar Ahmed Othman; Fadhil T. Aula (Zanco Journal of Pure and Applied Sciences, 2023)
Solar thermal is a kind of renewable energy that converts solar radiation to heat using a concentrator that concentrates the heat in the focal point. The receiver is located in the focal and transfers heat to the flowed water, rising the water temperature beyond boiling. To harvest the most solar efficiency, a dual tracking system is used that tracks the sun during the daytime. This paper proposes implementing Arduino Uno dual axis tracking system for the solar parabolic concentrator dish. The tracking system is controlled and managed by using an Arduino microcontroller and light sensors. The proposed system has been installed in the city of Erbil and the testing results showed the success of the proposed system in which the dual tracking system tracked the sun precisely and the concentrator with the help of the receiver raised the flowed water to the desired temperature.